A Median Analysis of Factors Influencing Body Fatness in Urban School-Age Children in Cameroon. (3rd February 2019) - Niba, Loveline L.; Itor, Paul B.; Aurelie, Yemele K. Sibelle; Singam, Foba M.; Tange, Emmanuel A.; Atanga, Mary B.; Navti, Lifoter K.
Abstract : Background . Childhood overweight/obesity is a fast growing public health problem in developing countries. The adverse health consequences of obesity have been attributed to higher body fat levels and this has drawn overwhelming attention towards more accurate assessment of body fat. The goal of this study is to evaluate the relationships between selected behavioral factors and percentage body fat (%BF) estimated using bioelectrical impedance analysis in school-age children. Methods . A cross-sectional analysis was carried out in randomly selected 6- to 11-year-old children (507 boys and 501 girls). Percentage body fat was assessed using bioelectrical impedance analysis. The behavioral factors were reported by parents using a structured questionnaire. Multiple quantile regression analysis was used to evaluate the relationship between the selected behavioral factors and %BF. Results . With quantile regression, the daily consumption of fruits and vegetables, daily breakfast consumption, and high physical activity (>4–7 times/week) were significantly (p < 0.001 ) associated with a 4.95, 3.29, and 3.66 decrease in median %BF, respectively. Also, consumption of snacks (>3 times a day) (p < 0.001 ), high sedentary lifestyle (>3–6 hours/day) (p < 0.001 ), and motorization to school (p < 0.005 ) significantly increased the median %BF by 3.69, 3.01, and 1.39, respectively. The largest changes in median %BF were observed in girls. Conclusions . Efforts are needed using longitudinal studies to clarify the effects of these behavioral factors on %BF in different regions and ethnic groups of Cameroon and also to assess whether any observed differences are of clinical relevance.